The interstellar medium local to HD 10125 - Cichowolski, Silvina (2003)
Based on an H I line and 408- and 1420-MHz radio continuum survey carried out at the Dominion Radio Astrophysical Observatory (DRAO), the environment of the O star HD 10125 has been studied. In addition, complementary radio continuum images, as well as infrared data of the same region have been analysed. An arc-like structure is found in all the radio continuum data. From the 21 -cm line data, an H I minimum is found in the velocity range ‒27 to ‒32kms-1. Although HD 10125 is not at the centre of the H I cavity, its eccentric position is consistent with the observed stellar proper motion. The H I cavity and the continuum arc-like structure show an excellent morphological correlation. The radio continuum emission has a spectral index (Sv ∼ vα) α = 0.0 ± 0.1, which establishes the thermal nature of the arc-like feature. The dust temperature obtained from the infrared data is higher in the area where the continuum emission is present. A distance of 3 kpc is derived for the star, the H I cavity and the radio continuum structure. We conclude that all the features we have found are physically related to each other. The O star has enough energetic photons to both ionize the surrounding gas and heat up the dust and, through its powerful wind, also sweep up the H I and H II gas.